Empowering senior medical residents as resuscitation team leaders - Florence Morriello; Jade Quirion; Homun Yee; Rashmi Narendrula (BMC Medical Education)
Abstract Background A code blue is a medical emergency indicating a patient requiring immediate attention with a systematic hospital wide response handled in a team based approach. In academic hospital settings, medical trainees are first responders to code blues. As first responders, a senior resident is required to assume the code blue leader role. Aim: This study explores what non-technical characteristics define a code blue leader to be a good leader? Methods The study took place at the Northern Ontario School of Medicine. A qualitative methodology was applied. Semi-structured interviews were conducted sequentially. Results Ten senior residents were interviewed using semi-structured interviews. Three distinct themes emerged, namely: individual factors, factors influencing team work and organization factors. Results confirm that residents lack confidence in leading code blue teams. This feeling is influenced by personal, team and situational factors. Residents lack training in non-technical skills and as a result feel they don’t know how to lead a code blue team and feel they lack the necessary skills to work effectively in a code blue team, especially under pressure. Conclusions These data suggest that the lack of devoted training to non-technical skills, influences resident confidence, comfort, preparedness and functioning of resuscitative teams. Northern Ontario School of Medicine University REB approved, file number 6,021,198.